(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2018)
In current era to make the world safer place for upcoming generations, one must endeavor to raise the individual moral stature by giving consideration to spiritual in!elligence. Spiri lual intelligence is the mind’s capacity to handle real and spiritual aspects of life. This study explores the relationship between spiritual intelligence and iob efficiency of professionals in Delhi Region. The primary and secondary data were used in this research. Here, the sample size is taken of sixty professionals. The study shows that Spiritual Intelligence helps them to develop optimistic outlook towards life & work which in turn provides positive result to professionals. It hos been found in the research that Spiritual Intelligence enhances the work efficiency & effectiveness of their decisions. The study further explores that When spirituality will be completely embraced in our daily life, one will not only make a living in this physical world, but also make living a success, and experience every moment of life as new, every day as o day of uplift and blessing, and enioy lasting peace.